Analisis Penilaian Harga Saham PT. Bank Syariah Indonesia Tbk Berdasarkan Analisis Teknikal - Abdul Alimin; Dyah Suci Lestari; Siti Amaroh (Fakultas Ekonomi dan Bisnis Universitas Islam Nahdlatul Ulama Jepara, 2023)
This study aims to determine stock price movements and determine when it is appropriate to hold shares, buy shares and sell shares of PT. Bank Syariah Indonesia, Tbk in 2021-2022. Descriptive method is the method used in this research. Secondary data for February 2021-January 2022 in the form of daily time series data is the data used in this study. To analyze the method used is technical analysis in which the indicators are the Moving Average (MA), Relative Strength Index (RSI), and Bollinger Band (BB). The results of the study state a stock price movement that can be read with the three indicators and can know when is the right time to hold, buy and sell shares.